2010
DOI: 10.1007/s00217-010-1317-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric fields upon accumulation of magnesium in Saccharomyces cerevisiae

Abstract: Cultures of Saccharomyces cerevisiae were treated with PEF to improve accumulation of magnesium in the biomass. Under optimized conditions, that is, on 15-min exposure of the 20-h grown culture to PEF of the 2,000 V and 20-ls pulse width, accumulation of magnesium in the yeast biomass reached maximum 3.98 mg/g dm. It constituted 40% of the total magnesium in the medium. That accumulation significantly correlated against magnesium concentration in the medium. Neither multiple exposure of the cultures to PEF nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Biomass content was in the range 0.2–0.3 g/g d.m. Pankiewicz and Jamroz ( 2010 ) obtained the highest accumulation of magnesium in S. cerevisiae cells treated with PEF at twice the field strength than the one used in this study (4.0 kV/cm). At lower values of electric field strength (0.1–1.0 kV/cm) higher accumulation was not observed.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Biomass content was in the range 0.2–0.3 g/g d.m. Pankiewicz and Jamroz ( 2010 ) obtained the highest accumulation of magnesium in S. cerevisiae cells treated with PEF at twice the field strength than the one used in this study (4.0 kV/cm). At lower values of electric field strength (0.1–1.0 kV/cm) higher accumulation was not observed.…”
Section: Resultsmentioning
confidence: 61%
“…Turbidimetric measurements were run against pure water at λ = 600 nm, in 2 mm measurement cell. Amount of biomass was calculated using equation for the standard curve c (mg/mL) = (Ap + 0.1053):1.1511, where Ap apparent absorbance (Pankiewicz and Jamroz 2010 ).…”
Section: Biomass Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent these adverse changes, the microencapsulation process is used [10]. One of the encapsulation methods is the accumulation of minerals in the yeast cells of S. cerevisiae [11][12][13][14]. In the study of Kyyaly et al [15] it was demonstrated that feeding anemic rats with iron-enriched yeast is more efficient than inorganic treatment in recovery from iron deficiency.…”
Section: Of 19mentioning
confidence: 99%
“…This process is also used to assist drying and can also cause stress reactions in plant systems or cell cultures [21]. Previous research has shown that this technique can be used for enriching S. cerevisiae yeast with metal ions [11,22,23]. Iron enriched yeast biomass can potentially be an additional source of this element in diet, especially for vegans and vegetarians.…”
Section: Of 19mentioning
confidence: 99%